Efforts of Islamic religious education teachers in improving the reading and writing skills of the Quran among the residents of Banyon village - Siti Rohmaniah; Wakib Kurniawan; Husin Abdullah Aljufri Aljufri (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
The ability to read and write the Qur'an is one of the basic competencies that are important for Muslims. However, there are still many people, especially in rural areas such as Kampung Banyon, Sragen, who do not have adequate Qur'an reading and writing skills. This study aims to identify and describe the efforts made by Islamic Religious Education (PAI) teachers in improving the ability to read and write the Qur'an among residents of Kampung Banyon. This study uses a qualitative approach with a descriptive research type. Data collection techniques used are interviews, observations, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of the research show that the efforts made by Islamic religious education teachers to improve the ability to read and write the Al-Qur'an in Banyon Village are to create a program of Al-Quran reading and writing activities every Monday and Friday on a regular basis, an inclusive approach to all levels of society, and the formation of Al-Futuh Foundation.